Clinical and morphological features including expression of βig-h3 and keratan sulphate proteoglycans in Maroteaux-Lamy syndrome type B and in normal cornea. Issue 2 (1st February 2002) - Akhtar, Saeed; Tullo, Andrew; Caterson, Bruce; Davies, Janet R; Bennett, Kelly; Meek, Keith M
Abstract : Aim: To carry out a detailed morphological study of the cornea of a 16 year old female with a Maroteaux-Lamy syndrome (MLS). Methods: Following a penetrating keratoplasty in July 1999, ultrastructural changes in the cornea were examined using electron microscopy. Proteoglycans were visualised using cuprolinic blue dye; and βig-h3 and keratan sulphate were detected by immunoelectron microscopy. Results: The epithelial cells were degenerate and contained apoptotic nuclei. Proteoglycans were present in epithelial cells, intercellular spaces, and in swollen desmosomes. An abnormally large quantity of proteoglycans was present throughout the stroma. Keratocytes throughout the stroma had no cell organelles, were vacuolated, and contained a large quantity of abnormal proteoglycans. Labelling for βig-h3 was intense around electron lucent spaces in stroma. No labelling was seen in keratocytes or endothelial cells. In normal cornea, keratan sulphate labelling was regular throughout the stroma. In MLS VI type B cornea, keratan sulphate labelling was weak in the anterior stroma but very intense in the posterior stroma and in keratocyte lysosomes and vacuoles. Conclusion: A deficiency of aryl sulfatase B results in the deposition of keratan sulphate proteoglycan and other proteoglycans in lysosomes, causing the death of keratocytes and an abnormal build-up of proteoglycans in the stroma. This might be responsible for the lateral aggregation of collagen fibrils and impaired fibrillogenesis in MLS VI. Degenerate swollen keratocytes, together with gross changes in epithelial, stromal, and endothelial cells, would be expected to increase light scattering significantly in these corneas.